The modified Loughborough intermittent shuttle test: A performance test for use with games players - Ali, A.; Gant, N.; Foskett, A.; Moss, C.; Lynch, C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The Loughborough Intermittent Shuttle Test (LIST)1 was developed as a tool to reliably and accurately simulate the physiological demands of multiple-sprint sports such as soccer. The LIST protocol primarily involves periods of variable-intensity activity but since the sub-maximal exercise intensities are pre-determined and controlled by an audible signal it is not possible to examine self-selected aspects of running performance. Thus, it is not possible to assess fatigue-related decrements in exercise performance or whether any interventions increase `work output`. Therefore, the aim of this study was to investigate the reliability of a modified version of the LIST that included self-paced running for use as a performance tool. Methods: Fourteen male games players performed the protocol on two separate occasions with at least 7 days recovery between trials. The LIST comprises 6 x 15-min blocks of `prescribed` variable-intensity exercise (walking, sprinting, brief recovery, running and jogging) where participants exercise in time to audible signals. The modified test comprised 4 x 15-min blocks of `prescribed` activity followed by 2 x 15-min blocks of `self-paced` running (i.e. no audible signals). Participants were instructed to replicate the relative intensities of the prescribed exercise during the self-paced period. Various performance indicators were recorded during the protocol. Body mass (BM) was measured pre and post exercise while heart rate (HR) and blood lactate ([La]) were examined routinely. Participants were given 3 ml•kg-1 BM water during the 3-min rest periods between exercise blocks. Results: A correlation of r = 0.82 (P<0.01) and coefficient of variation (CV) of 1.7% for distance covered indicate good relative and absolute reliability. However, participants covered 1.4 ± 1.7% greater distance in Trial 1 (12.85 ± 0.26 km) vs. Trial 2 (12.67 ± 0.37 km, P=0.01). Distance covered was significantly less during the self-paced running period relative to prescribed activity (P<0.05). Percentage time spent in each activity was not different between trials (P>0.05) but average running velocity was higher in Trial 2 (P=0.01). Sprint performance was similar between trials (P=0.38) with a CV of 5.6%. There was no difference in BM loss (P=0.84) or mean HR (P=0.98) between trials but mean [La] was higher in Trial 1 (P=0.01). Conclusions: Incorporating self-paced exercise within the existing LIST test appears to be a sensitive means of quantifying key performance variables, provided participants are adequately familiarised with the exercise protocol. The protocol successfully detects the decay in running performance that occurs during the latter stages of exercise.